Effects of Sevoflurane Exposure During Mid-Pregnancy on Learning and Memory in Offspring Rats: Beneficial Effects of Maternal Exercise - Wu, Ziyi; Li, Xingyue; Zhang, Yi; Tong, Dongyi; Wang, Lili; Zhao, Ping (Frontiers in Cellular Neuroscience, 2018)
Effects of sevoflurane exposure during mid-pregnancy on learning and memory in offspring rats: beneficial effects of maternal exercise Fetal exposure to general anesthetics may pose significant neurocognitive risks but methods to mitigate against these detrimental effects are still to be determined. We set out, therefore, to assess whether single or repeated in utero exposure to sevoflurane triggers long-term cognitive impairments in rat offspring. Since maternal exercise during pregnancy has been shown to improve cognition in offspring, we hypothesized that maternal treadmill exercise during pregnancy would protect against sevoflurane-induced neurotoxicity. In the first experiment, pregnant rats were exposed to 3% sevoflurane for 2 h on gestational (G) day 14, or to sequential exposure for 2 h on G13, G14 and G15. In the second experiment, pregnant rats in the exercise group were forced to run on a treadmill for 60 min/day during the whole pregnancy. The TrkB antagonist ANA-12 was used to investigate whether the BDNF/TrkB/Akt signaling pathway is involved in the neuroprotection afforded by maternal exercise. Our data suggest that repeated, but not single, exposure to sevoflurane caused a reduction in both histone acetylation and BDNF expression in fetal brain tissues and postnatal hippocampus. This was accompanied by decreased numbers of dendritic spines, impaired spatial-dependent learning and memory dysfunction. These effects were mitigated by maternal exercise but the TrkB antagonist ANA-12 abolished the beneficial effects of maternal exercise. Our findings suggest that repeated, but not single, exposure to sevoflurane in pregnant rats during the second trimester caused long-lasting learning and memory dysfunction in the offspring. Maternal exercise ameliorated the postnatal neurocognitive impairment by enhancing histone acetylation and activating downstream BDNF/TrkB/Akt signaling. Keywords: general anesthesia, mid-pregnancy, learning and memory, maternal exercise, brain-derived neurotrophic factor INTRODUCTION A large number of studies in both humans and animals have demonstrated that exposure to anesthetic agents during neurodevelopment triggers neurodegeneration and subsequent long-term neurobehavioral abnormalities, such as learning and memory impairment (Andropoulos and Greene, 2017; Barton et al., 2017; Fodale et al., 2017). Most previous animal studies focused on neonates (especially rodents in the first week after birth since this is a period of rapid